Effect of Agricultural Residues Based-Compost on the Yield of Amaranthus hybridus L. (Amaranthaceae) in Gbado-Lite City, Nord-Ubangi (Democratic Republic of the Congo) - Koto-te-Nyiwa Ngbolua; Zuangbo Innocent; Molongo Medard; Masengo Ashande Colette; Djolu Djoza Ruphin; Yabuda Honore; Gedeon Ngiala Bongo; Gbolo Zoawe Benjamin; Monde-te-Kazangba Godefroid (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
An experimental study was conducted in Gbadolite city to develop composts from peanut (Groundnut) and maize residues alone or combined. The study found that plots modified with compost based on peanut (Groundnut)  residues combined with corn residues are of good quality compared to  non-waste compost combined and unamended plots as indicated by the average values of plant height (91.9±0.79 cm vs. 54.0±1.35 cm), diameter at the collar (12.66±0.47 mm vs. 9.00±1.41 mm); number of leaves ( 20.6±0.47 vs. 15.6±0.47); leaf lengths (23.5±1.17 cm vs. 19.4±1.92 cm ); leaf widths (7.32±0.44 cm vs. 6.34±0.68 cm) yield per hectare ( 22.63±0.67T/ha vs 11.51±2.85 T/ha ). It is therefore desirable that compost be characterized from a physical-chemical point of view (pH, minerals, C/N ratio, etc.) and considers the production of other plants grown on this substrate in order to assess its effectiveness.